Charge and energy transfer in a bithiophene perylenediimide based donor-acceptor-donor system for use in organic photovoltaics - Wenzel, Jan; Dreuw, Andreas; Burghardt, Irene (Physical chemistry, chemical physics, 2013)
The elementary charge and excitation energy transfer steps in a novel symmetric donor-acceptor-donor triad first described in Roland et al. Phys. Chem. Chem. Phys., 2012, 14, 273, consisting of a central perylenediimide moiety as a potential electron acceptor and two identical electron rich bithiophene compounds, have been investigated using quantum chemical methodology. These elementary processes determine the applicability of such systems in photovoltaic devices. The molecular structure, excited states and the photo-physical properties are investigated using smaller model systems and including solvation effects. The donor and acceptor π-systems are separated by an ethyl bridge such that the molecular orbitals are either located on the donor or acceptor moiety making the identification of locally excited versus charge transfer states straightforward.